Comparative aspects of metamorphosis in fejervarya limnocharis and fejervarya cancrivora (Amphibia : Anura) - Pui, Yong Min. (Universiti Malaysia Sarawak (UNIMAS), 2007)
The metamorphosis of Fejervarya limnocharis and Fejervarya cancrivora larvae was studied in the laboratory. The larvae of both Fejervmya species were grown under several control environments: the water temperature was in the range 22-25°C and one individual per receptacle. This study found that F. limnocharis took 52 days to reach Stage 43 (n = 2). Survivor rate was 33% with heavy mortality in the later stages (Stage 35 and above). SVL reached optimum growth at Stage 40, whereas tail length has reached optimum development and become fully elongated at Stage 41 and started to resorb from Stage 42 onwards. Fejervmya cancrivora larvae took 31 days to reach Stage 29 (n = 3). The longest duration of metamorphosis was observed in Stage 25, which took 11 days before preceding to Stage 26, from which stage, the metamorphosis day length decreased. Late stages of larvae of the two Fejervarya species can be distinguished based on tail shape and pattern, oral disc features and body size.